The Poetic Concept of Art of L.F. Dostoevskaya - Aleksandra V. Banchenko (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
L.F. Dostoevskaya’s oeuvre consists of short stories and two novels, together with a biography of F.M. Dostoevsky. Her fiction is perceived by researchers as largely autobiographical; her book about F.M. Dostoevsky as a father is considered the least reliable source of biography. Therefore a mixture of genres can be considered: her prose displays features of the poetics of autobiography; her documentary contains fiction, while the author’s discourse dominates the character of the book. This article discusses some features of the poetics of fiction and the documentary prose of L.F. Dostoevskyaya. Dostoevskaya’s works suggest that the narrator is close to the author, since in some works the narrator is an autobiographical narrator named Lyubov Feodorovna. This article presents elements of a narratological analysis of her oeuvre of novels and short stories; this can help the reader trace the connections between the perspectives of the protagonists and narrators. In some narrative structures, the positions of the protagonists and narrators become equivalent due to the extra-narrative roles of the latter. The article also provides a partial analysis of the main themes and motifs of her prose, indicating their connection to the work of F.M. Dostoevsky. In particular, we discuss the connection between Dostoevskaya’s prose and her father’s unfinished novel ‘Netochka Nezvanova’. Taken as a single text, the prose of the great writer’s daughter demonstrates features of the Bildungsroman.